Reformulation of the Position of Auxiliary State Institutions as Legal Standing Related to Authority Disputes of State Institution - Mirja Fauzul Hamdi (Kanun Jurnal Ilmu Hukum, 2021)
This research aims to examine the reformulation meaning of legal standing of state institutions in authority disputes cases between state institutions and the juridical implications of the legal standing of auxiliary state institutions as parties in the authority disputes cases of state institutions. Authority disputes may arise along with the development of state institutions based on their needs and interests in dealing with certain legal issues. This approach uses a normative method with descriptive analytical specifications. The results of the study show that the meaning of state institutions which can be the legal standing in the authority disputes cases between state institutions is not only interpreted by state institutions that are formed and given authority according to the 1945 Constitution. Auxiliary state institutions, which on the one hand carry out their functions as a form of derivation from the 1945 Constitution, can become state institutions litigating at the Constitutional Court. Regarding the implications of determining legal standing for state institutions that are formed by laws to litigate at the Constitutional Court, in fact it does not change the authority of the Constitutional Court itself according to Article 24c of the 1945 Constitution. The state institutions that become the legal standing at the Constitutional Court must of course be able to prove that their objectum litis is a derivation of the constitution.